Concise Guide to Optimization Models and Methods A Problem-Based Test Prep for Students - Ng, Xian Wen.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This concise text contains the most commonly-encountered examination problems in the topic of Optimization Models and Methods, an important module in engineering and other disciplines where there exists an increasing need to operate optimally and sustainably under constraints, such as tighter resource availability, environmental consideration, and cost pressures. This book is comprehensive in coverage as it includes a diverse spectrum of problems from numerical open-ended questions that probe creative thinking to the relation of concepts to realistic settings. The book adopts many examples of design scenarios as context for curating sample problems. This will help students relate desktop problem-solving to tackling real-world problems. Succinct yet rigorous, with over a 100 pages of problems and corresponding worked solutions presented in detail, the book is ideal for students of engineering, applied science, and market analysis.
Chapter1: Basic Concepts, Lagrangian Methods and Linear Programming Problems -- Chapter2: Non-linear Programming Problems with Constraints and Euler$1 (Bs Methods -- Chapter3: Complex Optimization Problems.s
Keywords: Industrial engineering; Production engineering; Mathematical optimization; Computer simulation; Industrial Management; Industrial and Production Engineering; Optimization; Computer Modelling; Industrial Management; Process Engineering; Mathematical optimization